Proceso atención de enfermería en escolar con insuficiencia renal aguda. - López Lara, Anderson Jefrey (2024)
The following clinical case study was applied to a schoolchild who presented a clinical picture of ±12 hours of evolution characterized by elevated temperature, oliguria, dysuria, edema in the lower limbs, headache, arthralgia, myalgia and general malaise. Upon monitoring vital signs, the patient's temperature was 39ºC, heart rate 120rxmin, respiratory rate 22rxmin and saturation 98%. During the physical assessment, the patient was conscious, oriented in time and space, with moist oral mucosa. There were no lesions in the oral cavity or pharynx. On auscultation, ventilated lungs are confirmed. Palpation reveals a soft, depressible abdomen, slightly painful in the hypogastrium and signs of edema in the lower limbs. A complete blood count, polymerase chain reaction test, chest and abdomen X-ray plus control electrolytes are requested. After having applied the Nursing Care Process based on the taxonomies, the expected results in this clinical case study were achieved. However, to achieve this objective, each nursing care had to be provided in a timely and effective manner according to this pathology, in order to restore the patient's state of health and well-being during their hospitalization.